Sosialisasi Sustainable Development Growth Industri di Era Digital - Sampetoding, Eliyah Acantha Manapa; Purba, Arini Anestesi; Pongtambing, Yulita Sirinti; Uksi, Rafika; Isabella, Mayati (PT Ininnawa Paramacitra Edu, 2024)
Sustainable development in the digital era is related to the integration of technology and digital innovation that supports environmentally friendly practices. Digital economy plays a significant role in promoting environmental innovation in production companies, leading to the application of environmentally friendly practices. This activity aims to socialize the important role of SDGs in guiding business strategies and innovation towards sustainability. Socialization methods are conducted through social approaches to participants through online socialization with 130 participants. This activity resulted in several strategies for implementing SDGs in the industrial field, including: (1) Data Identification; (2) Determining the data gap; (3) Determining the tools/methods for closing the gap; (4) Identifying objects starting from small-scale; (5) Measuring improvements and evaluating the effectiveness of the system.